Produksi Asam Asetat oleh Sel Acetobacter pasteurianus INT-7 Amobil pada Variasi Konsentrasi Etanol - Sri Luwihana; Endang Sri Rahayu; Slamet Sudarmadji; Kapti Rahayu (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
Acetic acid fermentation by Acetobacter pasteurianus 1NT-7 immobilized cells with alginate gel on various ethanol concentration was investigated. Immobilized acetic acid bacteria cells were prepared with alginate gel 3% concentration with ratio cell suspension and alginat gel 1:3 (v/v) and conditioning time 24 hours. Fermentation using 10% immobilized cells (beads), medium of fermentation is YEPE (yeast extract pepton ethanol) with three ethanol concentration 5%, 7,5% and 10% respectively. Fermentation is going on shaker incubator with condition 100 rpm, 30